2005
DOI: 10.1248/bpb.28.1444
|View full text |Cite
|
Sign up to set email alerts
|

Anti-atherogenic Effects of the Methanol Extract of Sorbus Cortex in Atherogenic-Diet Rats

Abstract: The present study was designed to examine whether the methanol extract of Sorbus commixta cortex (MSC) could prevent the development of atherosclerosis through regulating the vascular nitric oxide (NO) and endothelin-1 (ET-1) systems in atherogenic-diet rats. Our findings show that aortic NO production as well as endothelial nitric oxide synthase (ecNOS) expression was significantly decreased in atherogenic-diet rats compared with those in the control group. Aortic ET-1 expression was augmented in rats fed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
(37 reference statements)
1
23
0
1
Order By: Relevance
“…[47][48][49][50] Recent studies have reported that they possess antioxidant and anti-inflammatory properties. 33,34,[48][49][50][51][52][53][54] Oxidative damage and neuroinflammation are fundamental to the progression of AD; therefore, these plants would provide neuroprotective activity through their antioxidative and anti-inflammatory functions. Supporting this idea, we found that S. commixta intake significantly reduced ROS levels as well as rescuing the AD-like phenotypes in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] Recent studies have reported that they possess antioxidant and anti-inflammatory properties. 33,34,[48][49][50][51][52][53][54] Oxidative damage and neuroinflammation are fundamental to the progression of AD; therefore, these plants would provide neuroprotective activity through their antioxidative and anti-inflammatory functions. Supporting this idea, we found that S. commixta intake significantly reduced ROS levels as well as rescuing the AD-like phenotypes in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were extracted for western blot analysis as reported previously (Sohn et al, 2005). Then 50 μg protein samples were separated on a 10% SDS-PAGE gel and electrophoretically transferred to nitrocellulose membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of serum levels of cholesterol and lipoproteins in atherogenesis have been observed in a number of studies [35,43]. Cellular cholesterol homeostasis is important for the prevention of cardiovascular diseases.…”
Section: Food Intake (%)mentioning
confidence: 99%